Maternal and newborn vitamin D status and its impact on food allergy development in the German LINA cohort study. Issue 2 (18th December 2012) - Weisse, K.; Winkler, S.; Hirche, F.; Herberth, G.; Hinz, D.; Bauer, M.; Röder, S.; Rolle‐Kampczyk, U.; von, M.; Olek, S.; Sack, U.; Richter, T.; et al.
Abstract Background Vitamin D levels are known to be associated with atopic disease development; however, existing data are controversial. The aim of this study was to investigate whether corresponding maternal and cord blood vitamin D levels are associated with atopic outcomes in early infancy. Methods Within the LINA cohort study (Lifestyle and environmental factors and their Influence on Newborns Allergy risk), 25(OH)D was measured in blood samples of 378 mother–child pairs during pregnancy and at birth. Information about children's atopic manifestations during the first 2 years of life was obtained from questionnaires filled out by the parents during pregnancy and annually thereafter. Cord blood regulatory T cells (Treg) were detected by methylation‐specific PCR using a Treg‐specific demethylated region in the FOXP3 gene. Results The median maternal 25(OH)D3 level was 22.19 ng/ml (IQR 14.40–31.19 ng/ml); the median cord blood 25(OH)D3 10.95 ng/ml (6.99–17.39 ng/ml). A high correlation was seen between maternal and cord blood 25(OH)D3 levels, both showing a seasonal distribution. Maternal and cord blood 25(OH)D3 was positively associated with children's risk for food allergy within the first 2 years. Further, higher maternal 25(OH)D3 resulted in a higher risk for sensitization against food allergens at the age of two. Cord blood 25(OH)D3 levels were negatively correlated with regulatory T cell numbers. Conclusion Our study demonstrates that high vitamin D levels in pregnancy and at birth may contribute to a higher risk for food allergy and therefore argues against vitamin D supplement to protect against allergy.